Caspase-1-Dependent Pyroptosis of Peripheral Blood Mononuclear Cells Is Associated with the Severity and Mortality of Septic Patients. (29th February 2020) - Wang, Yuchang; Liu, Yukun; Liu, Qinxin; Zheng, Qiang; Dong, Xijie; Liu, Xinghua; Gao, Wei; Bai, Xiangjun; Li, Zhanfei
Abstract : Purpose . Pyroptosis has been known to play a vital role in the inflammation process which was induced by infection, injury, or inflammatory disease. The present study was aimed at evaluating the percentage of peripheral blood mononuclear cell (PBMC) pyroptosis in septic patients and assessing the correlation of PBMC pyroptosis with the severity and the mortality of septic patients. Methods . 128 trauma-induced patients with sepsis were enrolled in this prospective cohort study. Blood samples were collected, and PBMC pyroptosis was measured by flow cytometry within 24 hours after sepsis was diagnosed. Results . Percentage of PBMC pyroptosis was positively correlated with the acute physiology and chronic health evaluation (APACHE) II score and sequential organ failure assessment (SOFA) score (all P < 0.01 ). The area under the curve (AUC) for the percentage of PBMC pyroptosis on a receiver operating characteristic curve was 0.79 (95% confidence interval (CI), 0.68–0.90). A Cox proportional hazard model identified an association between an increased percentage of PBMC pyroptosis (>14.17%) and increased risk of the 28-day mortality (hazard ratio = 1.234, 95% CI, 1.014–1.502). Conclusion . The percentage of PBMC pyroptosis increases in septic patients, and the increased percentage of PBMC pyroptosis is associated with the severity of sepsis and the 28-day mortality of patients with sepsis.